DEKONSTRUKSI NASI GORENG JAWA - Nathaniel Setyo; Dendi Gusnandi (Media Bina Ilmiah, 2024)
Javanese Fried Rice is an iconic Indonesian dish that is rich in spices and has a distinctive taste. This journal aims to deconstruct javanese Fried Rice, dig deeper into its meaning and symbolism, and change the form of presentation to onigiri. The research method used was a quantitative experiment, with data collection through questionnaires filled in by 25 panelists. The research results show that this deconstruction was well received by consumers, with positive assessments on the aspects of taste, aroma, texture, appearance and overall quality. This research also reveals how Javanese Fried Rice is not just a delicious dish, but also a symbol of culture, tradition and identity of Indonesian people. By deconstructing Javanese Fried Rice into onigiri, this innovation shows that the essence of a traditional dish can be maintained in a more modern and practical form. The results of this research provide a significant contribution to the study of Indonesian culinary culture.